Abnormal uterine bleeding in peri-menopausal age: Diagnostic options and accuracy - Dasgupta, Subhankar (Springer-Verlag, 2011)
OBJECTIVES: Various diagnostic techniques have been evolved over the periods to determine the etiology of abnormal uterine bleeding in peri-menopausal women, but their accuracy has not been compared properly. In this study diagnostic accuracy of trans-vaginal sonography (TVS), saline infusion sonography (SIS) and dilatation & curettage (D & C) were compared with hysteroscopic guided biopsy to determine the etiology. METHODS: In this study, 252 patients had to undergo trans-vaginal sonography and saline infusion sonography in the same sitting followed by hysteroscopic-guided biopsy and dilatation and curettage. All the materials were sent for histopathological examination. RESULTS: In determining uterine pathology, positive likelihood ratio (PLR) of TVS, SIS and D & C are 2.81, 7.5 and 3.81 respectively considering hysteroscopy as standard. CONCLUSION: Sensitivity of SIS as a test for detecting pathology in abnormal uterine bleeding (AUB) is high and can be easily performed on out patient basis. D&C has a very low sensitivity and is unacceptable as a screening test for the same conditions.